PEMBUATAN BIOETANOL DARI NIRA NIPAH DENGAN ALAT HASIL REKAYASA TIPE P3HH-1 - Djeni Hendra; Sri Komarayati; Heru S. Wibisono (Jurnal Penelitian Hasil Hutan, 2016)
High consumption of fossil fuel causes energy crisis since its reserve is decreasing. This fact stimulates many studies to find out alternative energy as fossil fuels substitute. Bioethanol is considered as one of the most important source of alternative energy extracted fromplants.This research is aimed to provide tool engineeringrequired in producing bioetanol from Nypa fruticanssap. The engineering is consisted of two reactors. The first reactor can be used for pasteurization, sacarification and fermentation. The important second reactor is used as a distillation unit. The tool engineering has important advantage by using SSF (Simultaneous Sacarification and Fermentation) technique. By using this technique, processof pasteurization and fermentation can be carried out in onereactor. However the low levelof bioethanol flow rate becomes the weaknessof this tool . Theyield of Nypa fruticanssap was about 13.5% and the bioethanol contentof 70-94.5% with an averageof 84.8%. The yield of bioethanol distillation can be improved through the dehidration process. Bioethanol content can be increased from 94.5%to 98.5% by the dehidration process.